2020
DOI: 10.1016/j.bpj.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the pH-Dependent Parallel-Stranded d(CGA) Motif

Abstract: Non-canonical DNA structures that retain programmability and structural predictability are increasingly being used in DNA nanotechnology applications, where they offer versatility beyond traditional Watson-Crick interactions. The d(CGA) triplet repeat motif is structurally dynamic and can transition between parallel-stranded homo-base paired duplex and anti-parallel unimolecular hairpin in a pH-dependent manner. Here, we evaluate the thermodynamic stability and nuclease sensitivity of oligonucleotides composed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Besides, PS A and H produce a positive band at ∼280 nm. In contrast, the antiparallel W showed a negative band at ∼245 nm and a positive band at ∼280 nm. These structures also exhibit a hyperchromic shift at 260 nm along with an increase in temperature and melting temperatures ( T m ), as shown in Figure S2. All the results above have confirmed the formation of parallel/antiparallel dsDNA.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Besides, PS A and H produce a positive band at ∼280 nm. In contrast, the antiparallel W showed a negative band at ∼245 nm and a positive band at ∼280 nm. These structures also exhibit a hyperchromic shift at 260 nm along with an increase in temperature and melting temperatures ( T m ), as shown in Figure S2. All the results above have confirmed the formation of parallel/antiparallel dsDNA.…”
Section: Resultsmentioning
confidence: 98%
“…Thus, optimal and tailor-made Au BMNPs are discovered to be suitable for label-free SERS detection of parallel dsDNA. PS CGA (formed through ssDNA SS CGA ), 25,26 and H (formed through ssDNA Pu and RPy), as well as antiparallel dsDNA W (formed through ssDNA Pu and Py) 27 (Figure 1). As a result, the featured bands from parallel dsDNA can unambiguously distinguish parallel dsDNA from antiparallel dsDNA when the base composition of DNA strands is the same.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Self-assembled DNA nanostructures have the advantages of modularity, structural programmability, and the resulting extraordinary devices and materials can be used in various research fields. 2–13 The ability to accurately program the secondary structure of oligonucleotide assemblies via base pairing has resulted in the creation of extraordinary devices and materials. Seeman proposed that DNA lattices could host proteins of unknown structure and thereby facilitate structure determination.…”
Section: Introductionmentioning
confidence: 99%
“…Nucleotide conformations in a folded duplex play an important role in ligand binding, enzyme recognition, and DNA transcription/translation. Trinucleotide repeats (TNRs) of CNG and GNC (5′-to-3′, N = T, A, G, C) with abnormal amplification have been identified as the main cause of neurodegenerative diseases. , These TNRs can form hairpin structures looping out of the main duplex during replication, in which context, CG/GC base pairs subsequently accommodate N–N mismatches. , It has been found that the hairpin foldings of TNRs are dependent on the repeat parity. , Namely, the detailed hairpin structures of TNRs are determined by the even/odd repeat number, and slippage complicates further the hairpin structures . Furthermore, the strand polarity of TNRs also defines the detailed structures.…”
mentioning
confidence: 99%